2019
DOI: 10.2169/internalmedicine.1896-18
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss-associated Cognitive Impairment in the Elderly: A Community-based Study in Japan

Abstract: Objective Dementia is a major cause of disruption for a healthy life expectancy in Japan. It has been suggested that the number of teeth is a modifiable risk factor for cognitive impairment and dementia. We therefore examined the possible association between the cognitive function and the number of natural and artificial teeth in community-dwelling Japanese elderly individuals. Methods Among the participants in our prospective, community-based study, 210 elderly individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 38 publications
0
44
0
2
Order By: Relevance
“…Clinically, many cohort studies have demonstrated that poor oral health leading to tooth loss and periodontal diseases are major risk factors for the progression of cognitive impairment [8,9], and recently several studies indicated the association between tooth loss and cognitive function [10][11][12][13][14][15]. It has been suggested that tooth loss has effects on the progressive development of dementia due to chronic inflammation caused by periodontitis [15,16], the invasion of oral pathogens and their toxins into the brain [17], reduced masticatory forces [18,19], and neurodegeneration in the hippocampus [20].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, many cohort studies have demonstrated that poor oral health leading to tooth loss and periodontal diseases are major risk factors for the progression of cognitive impairment [8,9], and recently several studies indicated the association between tooth loss and cognitive function [10][11][12][13][14][15]. It has been suggested that tooth loss has effects on the progressive development of dementia due to chronic inflammation caused by periodontitis [15,16], the invasion of oral pathogens and their toxins into the brain [17], reduced masticatory forces [18,19], and neurodegeneration in the hippocampus [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that tooth loss is associated with steeper global cognitive decline [4,5], an increased risk for cognitive impairment [6][7][8] and dementia [9], as well as brain atrophy in cognitively normal older individuals [10]. One cross-sectional study found that jaw mobility, bite strength and complaints about AGING masticatory function were associated with variation in episodic memory and executive function [11].…”
Section: Introductionmentioning
confidence: 99%
“…Tooth loss can also impact facial appearance and therefore affect self‐esteem and socialization . Other systemic conditions, such as cognitive decline and peripheral arterial disease, as well as overall mortality, have been linked to tooth loss. Financial limitations have also been linked to reduced oral healthcare utilization among older adults in multiple countries, and increased oral health insurance coverage is associated with higher use of oral healthcare services …”
Section: Introductionmentioning
confidence: 99%